2023
DOI: 10.3390/cells12121643
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Penetrating Peptides as Valuable Tools for Nose-to-Brain Delivery of Biological Drugs

Lisa Benedetta De Martini,
Claudia Sulmona,
Liliana Brambilla
et al.

Abstract: Due to their high specificity toward the target and their low toxicity, biological drugs have been successfully employed in a wide range of therapeutic areas. It is yet to be mentioned that biologics exhibit unfavorable pharmacokinetic properties, are susceptible to degradation by endogenous enzymes, and cannot penetrate biological barriers such as the blood–brain barrier (i.e., the major impediment to reaching the central nervous system (CNS)). Attempts to overcome these issues have been made by exploiting th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 146 publications
(422 reference statements)
0
3
0
Order By: Relevance
“… 137 Furthermore, intranasal administration has emerged as a widely utilized approach in pharmaceutical delivery owing to several benefits, including prompt absorption, rapid initiation of action, noninvasive nature, minimal tissue damage, and straightforward application. 138 This study revealed significant variations in the effectiveness of drug delivery among different intranasal delivery nanomaterials. These variations were mostly independent of the physicochemical features of the pharmaceuticals delivered.…”
Section: Intranasal Deliverymentioning
confidence: 88%
See 1 more Smart Citation
“… 137 Furthermore, intranasal administration has emerged as a widely utilized approach in pharmaceutical delivery owing to several benefits, including prompt absorption, rapid initiation of action, noninvasive nature, minimal tissue damage, and straightforward application. 138 This study revealed significant variations in the effectiveness of drug delivery among different intranasal delivery nanomaterials. These variations were mostly independent of the physicochemical features of the pharmaceuticals delivered.…”
Section: Intranasal Deliverymentioning
confidence: 88%
“…With low cellular toxicity and high effectiveness, cell-penetrating peptide (CPP)-based delivery methods can successfully transport macromolecules across cellular membranes. 138 The BBB must be physically broken apart for the invasive mechanism to function, and nanomaterials must be transferred along paracellular channels to cross the BBB ( Figure 3 ). 153 The transient BBB disruption technique described above and local delivery strategy are part of the invasive mechanism, also known as the paracellular mechanism.…”
Section: Bbb Crossing Mechanismmentioning
confidence: 99%
“…Rapid clearance by the mucociliary system can shorten the drug’s contact with the nasal mucosa, thereby reducing its absorption and bioavailability [ 64 ]. Some studies suggest that the nanocomplex may evade mucociliary clearance, potentially prolonging drug release [ 65 , 66 ]. This underscores the importance of better understanding mechanisms that can enhance nasal drug delivery efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the original pharmacological activity stays preserved. With the parenteral route of administration, the activity of the drug per se does not change, but its delivered volume passing through the blood-brain barrier becomes insufficient (7).…”
Section: Introductionmentioning
confidence: 99%